Association of 24-Hour Blood Pressure With Urinary Sodium Excretion in Healthy Adults. (22nd February 2018) - van der Stouwe, Jan Gerrit; Carmeli, Cristian; Aeschbacher, Stefanie; Schoen, Tobias; Krisai, Philipp; Wenger, Giuditta; Ehret, Georg; Ponte, Belen; Pruijm, Menno; Ackermann, Daniel; Guessous, Idris; Paccaud, Fred; et al.
Abstract: BACKGROUND: While the positive relationship between urinary sodium excretion and blood pressure (BP) is well established for middle-aged to elderly individuals using office BP, data are limited for younger individuals and ambulatory BP measurements. METHODS: Our analysis included 2, 899 individuals aged 18 to 90 years from 2 population-based studies (GAPP, Swiss Kidney Project on Genes in Hypertension [SKIPOGH]). Participants with prevalent cardiovascular disease, diabetes, or on BP-lowering treatment were excluded. In SKIPOGH, 24-hour urinary sodium excretion was used as a measure of sodium intake, while in GAPP it was calculated from fasting morning urinary samples using the Kawasaki formula. Multivariable linear regression models were used to assess the relationships of 24-hour urinary salt excretion with office and ambulatory BP measurements. RESULTS: Mean age, ambulatory BP, sodium excretion, and estimated glomerular filtration rate in GAPP and SKIPOGH were 35 and 44 years, 123/78 and 118/77 mm Hg, 4.2 and 3.3 g/d, and 110 and 99 ml/min/1.73 m 2, respectively. A weak linear association was observed between 24-hour ambulatory systolic BP and urinary sodium excretion (β (95% confidence interval [CI]) per 1 g increase in sodium excretion (0.33 % (0.09; 0.57); P = 0.008). No significant relationships were observed for 24-hour ambulatory diastolic BP (β (95% CI) (0.13 % (−0.15; 0.40) P = 0.37). When repeating the analyses in different age groups, all BP indices appeared to have stronger relationships in the older age groups (>40 years). CONCLUSIONS: In these large cohorts of healthy adults, urinary sodium excretion was only weakly associated with systolic 24-hour ambulatory BP.